Delayed presentation of midgut volvulus in 70-year-old patient: A case report - Alanood Algufaidi, MBBS, MD; Salwa Bahabri, MBBS; Aziza Alameen, MBBS (Radiology Case Reports)
Midgut rotation is uncommon to present in adult age group and can be complicated by midgut volvulus. Our patient is 70-year-old male, who presented to the emergency department with abdominal pain and constipation for 4 days. Enhanced abdominal computed tomography scan (CT) was done and showed typical findings of midgut volvulus, which are inversion of the mesenteric vessels and whirlpool sign. Patient had an exploratory laparotomy in which adhesiolysis, Ladd's procedure and appendectomy were done. The patient had uneventful postoperative recovery and was discharged after 6 days. Midgut malrotation results from failure of the midgut to rotate around the axis of the superior mesenteric artery. The presentation in adults are usually nonspecific and is low on the differential diagnosis, making enhanced abdominal CT the modality of choice. Midgut volvulus should be considered in cases of unexplained abdominal pain or bowel obstruction, even in adult age group. It requires emergent surgical intervention, so proceeding with urgent CT imaging is crucial.